Prototyping and low-volume production - Thompson, Rob (Manufacturing guides, 2011)
This book features new content selected specifically for the needs of students who create prototypes, designs for low-volume production runs, and designs that utilize craft. With some 450 specially commissioned photographs and technical illustrations, it describes more than 30 manufacturing processes, from the traditional and established to emerging technologies